Pengamanan Citra Digital Menggunakan Algoritma Pohlig Hellman - ginting, wasit (UNIVERSITAS PELITA HARAPAN, 2019)
Image encryption is a technique to protect the confidentiality of images from illegal access. With image encryption, people who do not know how the image is hidden will not know how to open it. Encryption is needed because in today's digital era digital images are easily stored or transmitted through public channels such as the internet. Image transmission through public channels is prone to tapping and storing images in storage media prone to access by parties without authority. For this reason, it is necessary to do a cryptographic method to secure confidential images from parties who do not have the authority to understand the actual image. This study presents an image encryption algorithm using Pohlig Hellman's Algorithm. The Pohlig Hellman algorithm is an algorithm used to compute discrete logarithms in a multiplicative group whose rank is not a safe prime number.Cryptography, Image, Pohlig-Hellman